2020
DOI: 10.1016/j.clae.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Survey of future use of personal protective equipment in optometric practice

Abstract: Purpose: The aim of this project was to evaluate which personal protective equipment (PPE) eye care practitioners (ECP) will use during the next months and also what they will ask the patient to use in clinical practice. J o u r n a l P r e -p r o o f

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 3 publications
2
15
0
Order By: Relevance
“…However, the results of the present study suggest that most practitioners might have increased the frequency of this practice in the wake of the COVID-19 pandemic. These findings are in accord with the practice of other eye care workers previously surveyed [ 15 , 17 , 26 ]. However, an assessment of eye care professionals' comfort and the effect of artifacts from the use of PPEs on ophthalmic examinations remain to be determined.…”
Section: Discussionsupporting
confidence: 90%
“…However, the results of the present study suggest that most practitioners might have increased the frequency of this practice in the wake of the COVID-19 pandemic. These findings are in accord with the practice of other eye care workers previously surveyed [ 15 , 17 , 26 ]. However, an assessment of eye care professionals' comfort and the effect of artifacts from the use of PPEs on ophthalmic examinations remain to be determined.…”
Section: Discussionsupporting
confidence: 90%
“…This is vital as several procedures involve the practitioner to be in close proximity to patients and as such proper use of PPE is essential. A survey of Optometrists and Opticians conducted in Austria, Germany and Switzerland reported that over 50% of the ECPs planned to wear masks during refraction, contact lens fitting and practiced hand washing and disinfection before performing procedures [31]. However, training in the use of PPE is important to avoid the ECP being infected.…”
Section: Discussionmentioning
confidence: 99%
“…As contact lens practitioners exited the first lockdown and returned to work, they were grateful that their contact lens busines survived due to monthly payment schemes for regular replacement lenses [19]. Precautions were in place, such as slit lamp guards, additional cleaning between patients, and personal protective equipment [20,21]. Chair time became more precious after lockdown and most practices reserved appointments slots for emergency and priority patients.…”
Section: Times They Are A-changin For Contact Lens Practicementioning
confidence: 99%